(x, y, z) = f the system is inconsistent, enter INCONSISTENT.)

Algebra
Tutor: None Selected Time limit: 1 Day


 
x + y + z = −1
y − 3z = 10
2x + y + 5z = −13

(xyz) = 

  
Apr 21st, 2015

The system is inconsistent because if you add to the third equation the second one and the first one multiplied by -2, then you get 

x(2 + 0 - 2) + y(1 + 1 - 2) + z(5 +(-3) - 2) = -13 + 10 - 2(-1) 

or 0 = -1.

Apr 21st, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Apr 21st, 2015
...
Apr 21st, 2015
Mar 27th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer